دور مدير المدرسة كمشرف التربوي لتحسين أداء مدرّسي اللغة العربية - Zakiyatul Abidah; Nurul Jannah (Program Studi Pendidikan Bahasa Arab bekerjasama dengan Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan., 2021)
Abstract: The role of the headmaster as an educational supervisor has a significant impact on the success of educational programs. Because the objectives of supervision activities to improve teacher performance. The objectives of this research are to describe the role of the headmaster as an educational supervisor, the school principal's efforts to improve the performance of Arabic language teachers and techniques used by the headmaster to improve the performance of Arabic teachers. The results of this research are expected to be able to provide input to the headmaster and Arabic language teachers about the role of the headmaster as an educational supervisor so that he can improve the performance of Arabic teachers. As for the results of the search for the role of the headmaster as an educational supervisor to improve the performance of Arabic language teachers is (1) the role of the headmaster of the school to improve the performance of language teachers to get a positive response to Arabic teachers because he can grow the motivation of Arabic teachers, (2) gives the school principal the motivation for Arabic language teachers to always participate in the competition that takes place outside the school or inside the school and then increase the knowledge of Arabic teachers through educational seminars and seminars for educational media and then increase the innovation of language teachers Arabic then hold lesson studies are learning the teacher in the classroom and other teachers look and send Arabic teachers to study, (3) techniques that apply the headmaster to improve the performance of Arabic teachers to improve the performance of Arabic teachers are individual techniques and collective techniques. Individual techniques include separate visits and private, formal and informal conversations. Group techniques include teacher meetings.